Efficiency of an increase in the radiation stability in various regions of the absorption spectrum of coatings based on TiO2 powders modified by SiO2 nanoparticles; Russian Physics Journal; Vol. 55, iss. 7 - Mikhailov M. M.; Remnev (Remnyov) G. E. Gennady Efimovich; Dzhabiev S. A.; Sazonov R. V. Roman Vladimirovich (2012, 2012)
Title screen